PERAN DUTA WISATA DALAM MEMPROMOSIKAN PARIWISATA KABUPATEN SOLOK - Randa "; Syofia Achnes (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The purpose of this research is to understand the role in promoting tourism ambassador Solok Regency tourism.This Research carried out in the Tourism and Culture Solok Regency. To achieve the goal is meant, in writing bachelor theses qualitative analysis methods are used descriptive. Where I give the impression tourism ambassador role and tourism objects clearly and systematic. This analysis based on the data obtained from both libraries and observation, namely or directly in field by doing interviews directly to informers that are considered to be able to give a clear associated with the problems that are examined.The Ambassador tourism was symbolic of the district level solok to tourism. That is the ambassador tourism in title as transmitted through air (male sex organ) and the European Union (women). Ambassador role tour which will be done through three promotion mix that is as follows: our through our sales is the role tour ambassador met face-to-face with the community/visitors when they were events event of the exhibition, the promotion through public relations at the ambassador role tourism information reported to attract tourists to come to Solok district, and the promotion through the information from mouth to mouth that ambassador role tour to convince people with pengalam which are related to the tourists interested in visiting tourism Solok Regency. During the time that has been done is a promotion that people are those least represented by the Ambassador subjoin Tourism based on events that are made by Tourism Solok district such as the exhibition, in events tour de singkarak culture week, west Sumatra, Indonesian Independence Day Solok district, a pageant transmitted through air European Union west sumatra, and so on. This is a routine activity performed by the ambassador tourism solok district every year. The role that has been carried out the ambassador tourism during this more or less has progress at the solok district to tourism, with various promotion and event on.Key words: The role , The Ambassador visit, Promotion, Tourism